Iodium intake, history of breastfeeding, growth and development of toddler aged 13–23 months at Srumbung, Magelang - Gloria Nirmayanty; Metty Metty; Untung S. Widodo (Ilmu Gizi Indonesia, 2019)
Background: The age of 0–2 years is the golden period because this is period of the fastest development of brain nerve. Breast milk contains iodine which is useful to maximize the process of growth and development of children. Iodine deficiency can also cause cretinism, usually occurring in endemic hyacinth areas such as at Srumbung. Objective: To determine the relationship between iodine intake and establishment of breastfeeding toward the growth and the development of toddler aged 13–23 months in three villages in Srumbung, Magelang City. Methods: This was survey study with cross sectional design. The study was conducted from April to May 2018 in Ngablak, Ngargosoko and Srumbung. The population were 110 toddler aged 13–23 months. Subjects were 86 children and were taken with proportional random sampling. Data of iodine intake, history of breastfeeding, and developmental were collected through interviews, while anthropometric data were obtained through direct measurement. Data were analyzed using Chi Sqare test with CI 95%. Results: The statistical analysis showed the maternal iodine intake and child growth had p =0,350, maternal iodine intake with child development had p=0,170, history of breastfeeding with child growth had p=0,130 and history of breastfeeding with child development had p=0.004. Conclusion: There was no relationship between maternal iodine intake and child growth, maternal iodine intake and child development, and history of breastfeeding and child growth. There was relationship between establishment of exclusive breastfeeding with development.